PENYUSUNAN KLASIFIKASI ARSIP AUDIO PADA MUSEUM MUSIK INDONESIA - Erlangga Andi Sukma; Rena Feri Wijayanti; Izzatul Ulya; Fatkhur Rochman; Zhulvardyan Armayrishtya; Muhammad Iqbal (Jurnal Pengabdian kepada Masyarakat, 2026)
The management of archives is gaining growing importance, particularly within museums. Well-structured and easily retrievable archives not only streamline day-to-day activities but also enhance overall efficiency and productivity. Nevertheless, many museums continue to struggle with effective archives management. Therefore, it becomes crucial for curators to adopt and implement proper archive classification systems to safeguard collections and ensure ease of retrieval. Specifically, the classification of audio archives requires the systematic and logical arrangement of archives to facilitate fast and straightforward access. This system proves especially valuable for accessing information related to the history of world music, including Indonesia. However, several museum curators have yet to apply proper classification methods. For instance, the Museum Musik Indonesia organizes its collections according to general practices but still encounters challenges in retrieval due to the lack of a structured classification framework. To address this issue, a community service program was carried out using a participatory approach that included four stages: counseling, discussion, mentoring, and evaluation. The establishment of an audio archive classification system will make it easier to locate and access archives whenever needed.